Inheritance System of Bugis Community in District Tellu Siattinge Bone, South Sulawesi (Perspective of Islamic law) - Tarmizi, Tarmizi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
Each region has different inheritance traditions, including in the Bugis community in Tellu Siattinge District, Bone Regency. This study aims to determine the distribution system of the Bugis heritagein Tellu Siattinge District, Bone Regency then examined in the perspective of Islamic law. This type of research is a qualitative research and research data was collected through document studies, observations and interviews with the community. The results showed that the transfer of assets was generally carried out before the testator died through grants or willswhich is divided by deliberation while assets that have not been divided will be distributed after the heir dies as inheritance. The main heir who inherits only children, the determination of the portion received by the heirs depends on the agreement and the portion received by men and women is generally generalized. The system of inheritance is not appropriate according to Islamic law, especially in fiqh mawāriṡ, but because the distribution is done based on mutual agreement (islah), this is permitted with a record as long as the rights of each heir are taken into account and there is no conflict in the distribution of inheritance.